Emancipación y trama vincular: los afectos subyacentes a las relaciones de autoridad - Coronado, Mónica (2024)
This work addresses the teaching authority in a context of the fragility of social ties, from its educational commitments, its emotional configuration and its ethical root. It is conceived as an institutionally circumscribed link, dynamic, changing, unstable and necessary for the educational task, in the dual role that Arendt attributes to it, of caring for the world of the newcomers, as well as that very subject that comes to revolutionize it. It is considered in relation to what was raised by Sennet that it is one of the four distinctly social emotions, as it establishes a bond and an expression of feelings towards other people. It is enabled at the beginning of life, in the family, pre-political context, by the interplay between tenderness and the absolute dependence and indefence of the newcomer, then legitimized in the public sphere of the school by the same responsibility to educate, in an emancipatory key. Like every emotional expression and expression of power, it is often the subject of suspicion because of its frequent excesses and overflow; nevertheless, it is necessary and ethical when it is sustained by the intention to educate, as in trust and mutual respect, as well as when it can be challenged, confronted and tested in the majesty of development. Pedagogical authority, which transcends the school bond between adults, whether as a management team or teacher and adult staff of the school, and of these with students, can be thought of as a key of bond, of bond of trust, loving, reciprocal and solidarity.